The commencement age of training and its effects on technical preferences and achievements attained by judo contestants - Lech, G.; Sterkowicz, S. (Human Movement, 2004)
Purpose. The aim of the present study was to determine the impact of training implemented at an early school age on technical schooling as well as on sports achievements attained by judo contestants. Implementation of the above-mentioned tasks - according to the authors - may supply information on the optimal age at which to undertake training activities by judo competitors, as well as may be an indication regarding determination of technical schooling direction during this period of development.